Histone lactylation as a driver of metabolic reprogramming and immune evasion - Cai Qiaoting; Deng Wei; Zou Yutian; Chen Zhe-Sheng; Tang Hailin (Medical Review)
Lactate is the end product of glycolysis, and extensive research has shown that lactate participates in various pathophysiological processes. Along with associated hydrogen ions, lactate typically functions as an immunosuppressive negative factor and plays a crucial role in tumor metabolic reprogramming. The recently discovered lactylation is a novel epigenetic modification that, similar to other epigenetic modifications, modifies histones to alter chromatin spatial configuration, thereby affecting DNA accessibility and regulating gene expression. More importantly, the degree of lactylation is closely related to local lactate concentrations, establishing a link between epigenetics and metabolic reprogramming. During cellular metabolism, lactate accumulation promotes histone lysine lactylation in cancer cells and immune cells such as macrophages and T cells, playing an essential role in tumor immune evasion and resistance to immunotherapy. This paper details the role of lactylation modifications in cancer immune evasion and resistance to immunotherapy, providing novel therapeutic directions and targets for cancer treatment.